1986
DOI: 10.1002/chin.198641112
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: New Syntheses of 2‐Acylbenzofurans, 2‐Acylindoles, 2‐Indolylcarboxylates, and 2‐Quinolones by Intramolecular Wittig Reaction.

Abstract: The phosphonium salts (I) react with the acid chlorides (II) immediately to give the benzofurans (III) (the intermediate 2‐(α‐ketoacyloxy) salts are not isolated).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…33 Ethyl (3-Octadecanoylindol-2-yl)acetate (7). To the refluxed solution of N,N-dimethyloctadecanamide (374 mg, 1.2 mmol) and POCl3 (153 mg, 1 mmol) in dry benzene (10 mL) was added in one portion the solution of ethyl (indol-2-yl)acetate ( 6) 49 (203 mg, 0.4 mmol) in dry benzene (3 mL). After 3 h an aqueous sodium acetate (1 g/4 mL) was added, and refluxing was continued for an additional 15 min with vigorous stirring.…”
Section: Methodsmentioning
confidence: 99%
“…33 Ethyl (3-Octadecanoylindol-2-yl)acetate (7). To the refluxed solution of N,N-dimethyloctadecanamide (374 mg, 1.2 mmol) and POCl3 (153 mg, 1 mmol) in dry benzene (10 mL) was added in one portion the solution of ethyl (indol-2-yl)acetate ( 6) 49 (203 mg, 0.4 mmol) in dry benzene (3 mL). After 3 h an aqueous sodium acetate (1 g/4 mL) was added, and refluxing was continued for an additional 15 min with vigorous stirring.…”
Section: Methodsmentioning
confidence: 99%
“…A mixture of 2-hydroxybenzylalcohol (16.27 mmol) and PPh 3 •HBr (16.27 mmol) in CH 3 CN (40 mL) was stirred under reflux for 2 h. The solid formed was filtered and washed with CH 3 CN to give the desired compounds IIa-IIc [20,24,25].…”
Section: General Procedures For the Preparation Of 2-hydroxybenzyltri...mentioning
confidence: 99%
“…The desired Wittig reagent was readily prepared from the conveniently substituted 2-hydroxybenzyl alcohol Ia-c and triphenylphosphine hydrobromide (PPh 3 •HBr) [20][21][22][23]. The key step for the formation of the benzofuran moiety was achieved by an intramolecular reaction between 2-hydroxybenzyltriphosphonium salts IIa-c [20,24,25], and the appropriate benzoylchloride.…”
Section: Chemistrymentioning
confidence: 99%
“…Accordingly, the literature describes several preparations of ethyl 2-(1H-indol-2-yl) acetates. For example, Capuano et al demonstrated that the intramolecular Wittig reaction of 2-[(ω-alkoxycarbonylacyl) amino] benzyltri-phenylphosphonium salts produced 2-(1H-indol-2-yl)-acetate with a 78% yield [21]. Furthermore, Moody et al reported that reductive cyclisation of the ethyl 4-(2-nitropheny)-acetoacetate using titanium(III) chloride in aqueous acetone gave 2-(1H-indol-2-yl) acetate with a 75% yield [22].…”
Section: Introductionmentioning
confidence: 99%